Aluminium silicate fertilization in the quality of wheat seeds under salt stress - Castellanos, César Iván Suárez; Deuner, Cristiane; Rosa, Mariana Peil da; Bohn, Alberto; Barros, Antonio Carlos Souza Albuquerque (Agrarian, 2015)
Wheat is used as raw material in the production of several foods and it is the first cereal as in the world production of grains. However, the agricultural production is limited for the salinity effect in about 50% of irrigated areas in the world. An alternative to reduce the salt stresses caused in the plants is the silicon use. The objective of this study was to evaluate the fertilizing effect with aluminum silicate using kaolin as a source, on seed quality of wheat produced under salt stress. The experiment was accomplished in greenhouse using wheat seeds of Quartzo cultivar sowed in pots of 10 L containing soil and maintained until harvest. The kaolin (77.9% SiO2) was applied in doses of 0 (control); 1,000; 2,000 and 3,000 kg ha-1. Salt stress was simulated through irrigation with NaCl solutions in the concentrations of 0 (control), 8 and 16 mM. Agronomic characteristics and the physiologic seed quality were evaluated. The results showed that the salt irrigation caused decrease in the number of ears per plant, number of ears with seeds, in the weight of the ears without threshing and in the weight of the produced seeds. The aluminum silicate use increased the weight of a thousand seeds independent of the presence of salt stress. Silicon application contributed to increase the percentage of germination of the produced seeds when the plants were not exposed to the salt stress.